Analysis of Factors that Affecting Cost Consciousness in Non-Profit Organizations - Dody Hapsoro; Maria Elly Budiarti (The Indonesian Journal of Accounting Research, 2017)
Abstract: The purpose of this study was to examine the effect of formal authority structure, accounting information system characteristics, work motivation and informal authority structure to cost consciousness mediated by manager behavior in decision control and decision management. The results of this study are expected to contribute to the development of theory, especially the theory of accounting behavior and add to managerial practices in improving the effectiveness and cost efficiency through the behavior of care costs. The research data is taken from non-profit organizations that provide educational services. Questionnaires were distributed to middle managers and structural officials in educational institutions. There are 250 questionnaires sent to respondents with a response rate of 62.8 percent. The analysis was done by using a two-step approach from SEM technique with Amos. The results show that formal authority structure has a positive effect on manager behavior in decision control and decision management. Characteristics of accounting information systems have a positive effect on manager behavior in decision control and decision management. Work motivation has no effect on manager behavior in decision control and decision management. The structure of informal authority has a positive effect on manager behavior in decision-making and decision management. Decision control and decision management have a positive effect on cost consciousness. The formal structure of authority and the structure of informal authorities have proven not to affect cost consciousness.Abstrak: Tujuan penelitian ini adalah untuk menguji pengaruh struktur kewenangan formal, karakteristik sistem informasi akuntansi, motivasi kerja dan struktur kewenangan informal terhadap kepedulian biaya yang dimediasi oleh perilaku manajer dalam pengendalian keputusan dan manajemen keputusan. Hasil penelitian ini diharapkan dapat memberi kontribusi untuk pengembangan teori, khususnya teori akuntansi keperilakuan dan memberi kontribusi terhadap praktik manajerial dalam meningkatkan efektivitas dan efisiensi biaya melalui perilaku peduli biaya. Data penelitian ini diambil dari organisasi nirlaba yang menyediakan layanan pendidikan. Kuesioner dibagikan kepada manajer menengah dan pejabat struktural di institusi pendidikan. Ada 250 kuesioner yang dikirim kepada responden dengan tingkat respon 62,8 persen. Analisis dilakukan dengan menggunakan two step approach dari teknik SEM dengan Amos. Hasil penelitian menunjukkan bahwa struktur kewenangan formal berpengaruh positif terhadap perilaku manajer dalam pengendalian keputusan dan manajemen keputusan. Karakteristik sistem informasi akuntansi berpengaruh positif terhadap perilaku manajer dalam pengendalian keputusan dan manajemen keputusan. Motivasi kerja tidak berpengaruh terhadap perilaku manajer dalam pengendalian keputusan dan manajemen keputusan. Struktur kewenangan informal berpengaruh positif terhadap perilaku manajer dalam pengendalian keputusan dan manajemen keputusan. Pengendalian keputusan dan manajemen keputusan terbukti berpengaruh positif terhadap kepedulian biaya. Struktur kewenangan formal dan struktur kewenangan informal terbukti tidak berpengaruh terhadap kepedulian biaya.